2013
DOI: 10.1080/02673843.2012.751043
|View full text |Cite
|
Sign up to set email alerts
|

Dimensions of school-based violence to and by children: an overview of recent literature

Abstract: School violence, defined in a variety of ways, is a common feature of contemporary education systems. While there is little empirical evidence to indicate either a significant increase (or decrease) in the phenomenon, it is accurate to recognise that it is a concern which has been the focus of continued attention by politicians, administrators, teachers and parents in most countries. This paper provides a summary of recent literature on the issue. It scopes in particular the core issues of causation, incidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 33 publications
1
5
0
1
Order By: Relevance
“…Our results corresponded with, findings from multiple studies in demonstrating that the involvement of peer leaders/mentors is effective in reducing VAC in and around schools (Cowie, 2011; Cowie & Hutson, 2005; Cowie & Olafsson, 2000; Garner, 2014). One reason is that the peer leader/mentor model is empowering for those students who fulfill this role and can improve their self-esteem (Cowie & Olafsson, 2000; Naylor & Cowie, 1999).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results corresponded with, findings from multiple studies in demonstrating that the involvement of peer leaders/mentors is effective in reducing VAC in and around schools (Cowie, 2011; Cowie & Hutson, 2005; Cowie & Olafsson, 2000; Garner, 2014). One reason is that the peer leader/mentor model is empowering for those students who fulfill this role and can improve their self-esteem (Cowie & Olafsson, 2000; Naylor & Cowie, 1999).…”
Section: Discussionsupporting
confidence: 90%
“…As VAC is a result of the interaction of a complex set of interpersonal, social, and political factors, programs can have greater effects if they include approaches that work on multiple levels of the social ecological model (Blaya & Debarbieux, 2008; Garner, 2014; Matjasko et al, 2012). Programs targeting VAC that include approaches such as community mobilization (Hillis, Mercy, Saul, et al, 2016; Semahegn et al, 2019; Yount et al, 2017), policy development and reform (Garner, 2014; Lee et al, 2013; Stanley et al, 2015; Ttofi & Farrington, 2010), advocacy (Ellsberg et al, 2015; Hillis, Mercy, Saul, et al, 2016; Semahegn et al, 2019), and capacity building (Garrard & Lipsey, 2007; Semahegn et al, 2019) in conjunction with school-based efforts have demonstrated effectiveness in several systematic reviews and meta-analyses. Likewise, interactive and engaging program materials and activities have been shown to be more effective than didactic methods alone (Clinton-Sherrod et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations